Study on Physical Properties of Inx Se1-x Thin Films Synthesized by Vacuum Evaporation Method - SUHAIL, Mahdi Hasan; IBRAHIM, Issam Mohammed; RAMIZY, Asmiet (Walailak Journal of Science and Technology (WJST), 2014)
Indium Selenide (InxSe1-x) thin films were synthesized in a sealed ampoule in a vacuum of 10-2 Torr using high purity elemental indium and selenium with different x concentration (0, 10, 15 % at.wt.) using vacuum evaporation technique. The structural properties of InxSe1-x alloys for (x = 10 and 15 % at. wt.) were examined by x-ray diffraction and exhibited a polycrystalline structure with hexagonal unit cell. The effects of the indium concentration and post deposition heat treatment on the structural and optical properties of the films were studied. The direct band gap of InxSe1-x thin films were estimated in the range (2.35 - 3.95) eV and the energy gap (Egopt) increases with increasing annealing temperatures. Optical constants (included refractive index (n), extinction coefficient (k), and real (er) and imaginary parts (ei) of dielectric constant) for the above films were calculated. The results were discussed in detail in relation with film recrystallization during the heating process. doi:10.14456/WJST.2014.82